Chitosan/sulfated locust bean gum nanoparticles: In vitro and in vivo evaluation towards an application in oral immunization - Braz, L. (2019)
This work proposes the design of nanoparticles based on locus bean gum (LBG) and chitosan to be used as oral immunoadjuvant for vaccination purposes. LBG-based nanoparticles were prepared by mild polyelectrolyte complexation between chitosan (CS) and a synthesized LBG sulfate derivative (LBGS). Morphological characterization suggested that nanoparticles present a solid and compact structure with spherical-like shape. Sizes around 180-200 nm and a positive surface charge between +9 mV and +14 mV were obtained. CS/LBGS nanoparticles did not affect cell viability of Caco-2 cells after 3 h and 24h of exposure when tested at concentrations up to 1.0 mg/mL. Two model antigens (a particulate acellular extract HE of Salmonella enterica serovar Enteritidis, and ovalbumin as soluble antigen) were associated to CS/LBGS nanoparticles with efficiencies around 26% for ovalbumin and 32% for HE, which resulted in loading capacities up to 12%. The process did not affect the antigenicity of the associated antigens. BALB/c mice were orally immunized with ovalbumin-loaded nanoparticles (100 mu g), and results indicate an adjuvant effect of the CS/LBGS nanoparticles, eliciting a balanced Th1/Th2 immune response. Thus, CS/LBGS nanoparticles are promising as antigen mucosal delivery strategy, with particular interest for oral administration. (C) 2017 Elsevier B.V. All rights reserved.